Determination of Labor Absorption on Tourism Sector in Denpasar City - Anggraeni, Tiara Puspita; Imaningsih, Niniek (PT. Riset Press International, 2024)
This research aims to show whether the dependent variable, namely Labor Absorption in the Tourism Sector, is influenced by the independent variables (Number of Tourists, Number of Tourist Attractions, Number of Hotels, and Number of Restaurants). This research was conducted using secondary data and time series with a time period of 15 years, namely from 2008 to 2022. Multiple linear regression analysis is a tool used to analyze and is processed using the SPSS 27 application program. The results of this research show that it is known in detail The overall simultaneousness of the independent variables has a positive and significant influence on labor absorption. Then the results of all independent variables, namely the number of tourists, have a significant effect on employment in the tourism sector in Denpasar City. Meanwhile, the number of tourist attractions, hotels and restaurants does not have a significant effect on employment in the tourism sector in Denpasar City.